A Novel Totivirus Naturally Occurring in Two Different Fungal Genera - Khalifa, Mahmoud E.; MacDiarmid, Robin M. (Frontiers in Microbiology, 2019)
Mycoviruses are widely distributed across different phyla of the fungal kingdom. Viruses that share significant sequence similarities have been reported in different fungi suggesting descendancy from a common ancestor. In this study, two fungal genera isolated from the same sample, Trichoderma koningiopsis isolate Mg10 and Clonostachys rosea isolate Mg06, were reported to have identical dsRNA profiles that consist of two virus-like, dsRNA elements (dsRNA-L and dsRNA-S). The complete sequence and genome organization of dsRNA-L from isolate Mg10 was determined. It is 4,712 nucleotides (nt) long and contains two non-overlapping ORFs that code for proteins with similarities to totiviruses and consequently the virus was given the proposed name trichoderma koningiopsis totivirus 1 (TkTV1/Mg10). The TkTV1/Mg10 genome structure resembles that of yeast totiviruses in which the region preceding the stop codon of ORF1 contains the elements required for -1 ribosomal frameshifting which induces the expression of an ORF1-ORF2 (CP-RdRp) fusion protein. Sequence analyses of viral dsRNA-L from C. rosea isolate Mg06 revealed that it is identical with that of TkTV1/Mg10. This was confirmed by northern blot hybridization and indicates very recent natural horizontal transmission of this virus between unrelated fungi. This is the first report of identical dsRNAs present naturally in two taxonomically distinct fungi.